Education on Green Computing Awareness at SMK Free Methodist Medan - Saragih, Mas Uhur Abdillah; Nasution, Muhammad Zikri Al Hakim; Simatupang, Rizky Agung (Prosiding Seminar Nasional Ilmu Komputer, Sosial Sains, Teknik dan Multi-Disiplin Ilmu, 2025)
Green computing education was conducted at SMK Free Methodist Medan on March 25, 2024, to improve students’ understanding of environmentally friendly information technology practices. The main issue identified was the low awareness of energy consumption in ICT devices, electronic waste management, and efficient computing behavior. The purpose of this study is to evaluate the effectiveness of the education program using lectures, demonstrations, and interactive discussions. The research method used is descriptive, with data collected through observation and questionnaires. The results show a 67% improvement in student understanding after the program. The activity had a positive impact on initial behavioral changes among students in adopting more energy-efficient ICT usage. These findings highlight the importance of implementing green computing education in vocational schools as a foundation for environmentally aware digital behavior.